PENGEMBANGAN PERTANIAN BUDIDAYA LORONG (ALLEY CROPPING) UNTUK KONSERVASI LAHAN KRITIS DI HULU DAERAH ALIRAN SUNGAI (DAS) CIMANUK, JAWA BARAT - Daru Mulyono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
The role and function of Cimanuk Watershed tend to declining, where total of critical area reach to a high of 131,384 ha from the total of 358,400 ha or about 36.6 %. In wet season debit of Cimanuk River reach 1,004 m3/second and in dry season reavh 4m3/second.Therefore the Debit Ratio of Cimanuk River reach to a high of 251, it is indicate that Cimanuk Watershed become very critical condition and need appropriate management especially in the upper watershed. One altervative of the watershed management is application of Alley Cropping system. The biomass from prunning of hedgerows Flemengia congesta have significant effect to land fertility through improvement of nutrients availability. Furthermore, the successful application of Alley Cropping system willlead to conserve land and water where it will support flood control, agricultural irrigation,fisheries development, electric generation, industrial development, etc.Keywords: agricultural, alley cropping, land conservation, watershed